SEJARAH TAREKAT DAN DINAMIKA SOSIAL - Lindung Hidayat Siregar (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2009)
Abstract: The History of Tareqah and Social Dynamics. The existence of tariqah has been differently responded by Muslim community. While some Muslims support and practice tariqah, others are highly critical and even rejected it as being part of Islamic tradition. However, regardless of the intellectual controversies surrounding it, tariqah has undergone very long history and has developed into a rich field of study. This article traces the historical roots of tariqah, analyses how it develop through times, and argues that tariqah contributes significantly in forming social norms among Muslims.Kata Kunci: tarekat, syaikh, silsilah, dan nilai ajaran tarekat